Chapter Il dibattito su "prerinascimento est-europeo" e "rinascita slava ortodossa" alla luce delle recenti ricerche - Garzaniti, Marcello (Biblioteca di Studi Slavistici, 2019)
Speaking at the IV International Congress of Slavists in Moscow (1958) on the Second South Slavic influence in Rus', Dmitrij Lichačëv presented his ideas on an "Eastern European Pre-Renaissance". Lichačëv's thesis received some criticism from the young Riccardo Picchio, who was then developing the idea of an "Orthodox Slavic revival (rinascita)". This article revisit the debate between these two important scholars, taking into account both subsequent developments in the research of each and more recent studies on the topic.